DISADVANTAGES OF ANABOLIC STEROID: A CASE STUDY - Sharma, Payal; Asthana Alok Kumar (International Journal of Ayurveda and Pharma Research, 2019)
The word steroid - we all know these are life saving drugs. Steroids have different meanings. Steroids are chemicals, often hormones that your body makes naturally. They help your organs, tissues, and cells do their jobs. Steroids can also refer to man-made medicines. We all know misuse of anything could be fatal. Nowadays anabolic steroids are very common especially in young adults going to gym for making muscles. Gym trainers are giving them steroids by saying and assuring that it will help them to build their muscle and body mass index. In some cases it can become life threatening too. Here in this article I’m going to present such case in which a young boy of just 25 years of age has taken such steroids and lands himself in deep trouble. He was healthy but the moment he joined gym, everything was ruined. He was diagnosed with AVN (Avascular Necrosis) of hip joint. AVN is a deadly pathology in which death of bone tissue occur due to lack of blood supply. Now he is not able to walk on his own and using wheel chair. So this article is basically awareness to young generation who are running behind this stuff and making their life hell.